The repertoire of iron superoxide dismutases from Leishmania infantum as targets in the search for therapeutic agents against leishmaniasis - Juan Carlos García-Soriano; Héctor de Lucio; Daniel Elvira-Blázquez; Mercedes Alcón-Calderón; Natalia Sanz del Olmo; Pedro A. Sánchez-Murcia; Paula Ortega; Francisco Javier de la Mata; Antonio Jiménez-Ruiz (Taylor & Francis Group, 2024)
Species of Leishmania and Trypanosoma genera are the causative agents of relevant parasitic diseases. Survival inside their hosts requires the existence of a potent antioxidant enzymatic machinery. Four iron superoxide dismutases have been described in trypanosomatids (FeSODA, FeSODB1, FeSODB2, and FeSODC) that hold a potential as therapeutic targets. Nonetheless, very few studies have been developed that make use of the purified enzymes. Moreover, FeSODC remains uncharacterised in Leishmania. In this work, for the first time, we describe the purification and enzymatic activity of recombinant versions of the four Leishmania FeSOD isoforms and establish an improved strategy for developing inhibitors. We propose a novel parameter [(V*cyt. c − Vcyt. c)/Vcyt. c] which, in contrast to that used in the classical cytochrome c reduction assay, correlates linearly with enzyme concentration. As a proof of concept, we determine the IC50 values of two ruthenium carbosilane metallodendrimers against these isoforms.